External validation of yonsei nomogram predicting chronic kidney disease development after partial nephrectomy: An international, multicenter study. (7th December 2022) - Abdel Raheem, Ali; Landi, Isotta; Alowidah, Ibrahim; Capitanio, Umberto; Montorsi, Francesco; Larcher, Alessandro; Derweesh, Ithaar; Ghali, Fady; Mottrie, Alexander; Mazzone, Elio; De Naeyer, Geert; Campi, Riccardo; et al.
Abstract: Objective: To externally validate Yonsei nomogram. Methods: From 2000 through 2018, 3526 consecutive patients underwent on‐clamp PN for cT1 renal masses at 23 centers were included. All patients had two kidneys, preoperative eGFR ≥60 ml/min/1.73 m2, and a minimum follow‐up of 12 months. New‐onset CKD was defined as upgrading from CKD stage I or II into CKD stage ≥III. We obtained the CKD‐free progression probabilities at 1, 3, 5, and 10 years for all patients by applying the nomogram found at https://eservices.ksmc.med.sa/ckd/ . Thereafter, external validation of Yonsei nomogram for estimating new‐onset CKD stage ≥III was assessed by calibration and discrimination analysis. Results and limitation: Median values of patients' age, tumor size, eGFR and follow‐up period were 47 years (IQR: 47–62), 3.3 cm (IQR: 2.5–4.2), 90.5 ml/min/1.73 m2 (IQR: 82.8–98), and 47 months (IQR: 27–65), respectively. A total of 683 patients (19.4%) developed new‐onset CKD. The 5‐year CKD‐free progression rate was 77.9%. Yonsei nomogram demonstrated an AUC of 0.69, 0.72, 0.77, and 0.78 for the prediction of CKD stage ≥III at 1, 3, 5, and 10 years, respectively. The calibration plots at 1, 3, 5, and 10 years showed that the model was well calibrated with calibration slope values of 0.77, 0.83, 0.76, and 0.75, respectively. Retrospective database collection is a limitation of our study. Conclusions: The largest external validation of Yonsei nomogram showed good calibration properties. The nomogram can provide an accurate estimate of the individual risk of CKD‐free progression on long‐term follow‐up.